Learning from documents: Applying new theories of materiality to journalism. (January 2015) - Neff, Gina
This article briefly reviews theories of materiality emerging in communication technology studies and organizational communication and then suggests three ways that journalism scholars might apply these theories to studies of news production. How journalists work, how journalism is shaped within newsrooms, the ways the news industry is changing, and ultimately, the effects of digital transitions can all benefit from including a focus on the 'objects of journalism'. First, objects, such as documents, help scholars describe the social settings where objects are found. Second, the objects of journalism help scholars uncover lines of authority, contexts of news routines, and richness and persistence of news practices. Third, studying the objects of journalism can help explain the persistence of so-called residual practices that might otherwise seem dysfunctional in digital news. Materiality theories can help journalism scholars explain the impact of the transition to digital news on the work and practices of journalists and the news industry as a whole.